Augustine’s Mature Understanding of John 5:19 and the Doctrine of Inseparable Operations - Beckwith, Carl L. 1973- (2022)
Augustine preached on John 5:19 in several anti-Arian works during the second decade of the fifth century. A close examination of his biblical text and trinitarian vocabulary provides sufficient clues to order these works chronologically and to observe the development of his reading of John 5:19. Augustine’s encounter with Latin Homoian arguments in the anonymous Sermo Arrianorum produces his mature understanding of John 5:19. He uses these insights to read other difficult texts on the Son and Holy Spirit in the Gospel of John and to express his mature understanding of the doctrine of inseparable operations.